Progesterone and estradiol exert an inhibitory effect on the production of anti-inflammatory cytokine IL-10 by activated MZ B cells. (August 2016) - Bommer, I.; Muzzio, D.O.; Zygmunt, M.; Jensen, F.
Abstract: The main message of this work is the fact that female sex hormones, progesterone and estradiol, whose levels significantly rise during pregnancy, inhibit the production of anti-inflammatory cytokine IL-10 with no apparent effect on pro-inflammatory cytokine TNF-α by activated MZ B cells. This is an important piece of information and helps to better understand how the maternal immune system controls the balance between immune tolerance and immune activation during pregnancy leading to the simultaneously acceptance of the semi-allogeneic fetus and the proper defense of the mother against pathogens during this critical period of time.